Screening for Language Difficulties in Disadvantaged Populations on Entry to Early Years Education: Challenges and Opportunities - Dockrell, Julie E.; Forrest, Claire L.; Law, James; Mathers, Sandra; Charlton, Jenna (Frontiers in Pediatrics, 2022)
Children from areas of social disadvantage experience delays in their language development, with significant numbers of children entering nursery classes with limited oral language. These difficulties are exacerbated when a child’s home language is not the language of instruction. This causes challenges for early years practitioners in developing the classroom language learning environment and in targeting resources for the children. There is a need for teachers to access tools to profile children’s language skills to inform their practice. Parent completed measures provide a viable means of assessing oracy skills on entry to nursery school. We examined the feasibility and validity of using a modified parental completed language checklist in areas of social disadvantage as an indicator of children’s language skills as they enter nursery classes. Children aged 3-4 years (n = 822) were recruited from deprived areas in England, a significant minority of the sample were second language learners. Oral language ability was assessed using child administered standardised measures, and parents reported on children’s language. We adapted the Language Use Inventory (LUI; O’Neill, 2007) to capture carer’s reports of the children’s structural language in the language of instruction and their home language (where appropriate). The final measure included six subscales from the original: use of simple words, requests for help, gaining attention, talking about activities/actions, interactions with others and building sentences. Children’s language abilities and non-verbal abilities were below norms on all of the standardized tests administered except non-word repetition. Factor analysis indicated that all the six scales of the adapted parent completed measure loaded on one language factor. The revised total scale score correlated significantly (p <.0005) with child assessed language measures, specifically expressive vocabulary, and grammar. Different patterns across gender, language status and parental education were examined. Sensitivity and specificity of the scale to identify children with the greatest delays was evaluated. These preliminary data indicated that parent reported information on children’s language skills at three years of age has the potential to provide a reliable indicator to inform pedagogy and practice at the start of nursery school. Study limitations are examined and avenues for future development explored.